2012
DOI: 10.2166/wst.2012.450
|View full text |Cite
|
Sign up to set email alerts
|

CFD analysis of sludge accumulation and hydraulic performance of a waste stabilization pond

Abstract: Sludge management in waste stabilization ponds (WSPs) is essential for safeguarding the system performance. Sludge accumulation patterns in WSPs are strongly influenced by the pond hydrodynamics. CFD modeling was applied to study the relation between velocity profiles and sludge deposition during 10 years of operation of the Ucubamba WSP in Cuenca (Ecuador). One tracer experiment was performed and three sludge accumulation scenarios based on bathymetric surveys were simulated. A residence time distribution (RT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 19 publications
4
32
0
1
Order By: Relevance
“…Alvarado et al (2012) determined that sludge accumulation and settling of sludge within waste stabilization ponds increases as water moves away from the inlet and the velocity decreases. Karteris et al (2005) created a temperature model within a covered anaerobic pond under unsteady state conditions.…”
Section: Modelingmentioning
confidence: 99%
“…Alvarado et al (2012) determined that sludge accumulation and settling of sludge within waste stabilization ponds increases as water moves away from the inlet and the velocity decreases. Karteris et al (2005) created a temperature model within a covered anaerobic pond under unsteady state conditions.…”
Section: Modelingmentioning
confidence: 99%
“…These high loadings were associated with the sludge accumulation, which was also the reason of unavailable data at the bottom of location 1 and 2 in FPs. According to the study of Alvarado et al [39] in this pond system, the sludge volume of the FPs reached up to 34% of the pond volume, which substantially reduced its active volume.…”
Section: Spatiotemporal Influences On the Oxygen Dynamicmentioning
confidence: 79%
“…This difference can be caused by the fact that the central area of the FPs had less sludge accumulation and flow turbulence, which promoted high density of algae located at this region [39]. On the other hand, the bathymetries in the study of Alvarado et al [16] on these MPs showed only a slight sludge layer growth in the maturation ponds that can be assumed negligible regarding the pond hydraulics.…”
Section: Spatiotemporal Influences On the Oxygen Dynamicmentioning
confidence: 89%
See 1 more Smart Citation
“…7.1 (and Table 7.1) are not effectively modelled using a lumped parameter approach, since there will be substantial variation in state variables across space. Particular examples where distributed parameter modelling is important include anaerobic biofilm reactors (including granular reactors), which can be modelled both in the micron scale through a biofilm model , as well as through an advective-diffusive (possibly plug-flow reactor) on the reactor scale (Batstone et al 2005), plug-flow semi-solid reactors (Dvorak 2012;Frear and Dvorak 2013), leach bed (including engineered landfill reactors) (Nopharatana et al 2003), and anaerobic digestion and stabilization lagoons (Alvarado et al 2012a;Alvarado et al 2012b). Even systems, which can be effectively represented by a single compartment from a biological perspective, may need a distributed parameter model for specific aspects, particularly those related to shear, mixing, or other operational considerations (BoyleGotla et al 2014).…”
Section: Complex (Distributed Parameter) Systemsmentioning
confidence: 99%